2010
DOI: 10.1523/jneurosci.5894-08.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for Motor Primitives in the Spinal Cord

Abstract: Motor primitives and modularity may be important in biological movement control. However, their neural basis is not understood. To investigate this, we recorded 302 neurons, making multielectrode recordings in the spinal cord gray of spinalized frogs, at 400, 800, and 1200 m depth, at the L2/L3 segment border. Simultaneous muscle activity recordings were used with independent components analysis to infer premotor drive patterns. Neurons were divided into groups based on motor pattern modulation and sensory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
199
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 241 publications
(214 citation statements)
references
References 178 publications
(132 reference statements)
15
199
0
Order By: Relevance
“…In a recent study published in The Journal of Neuroscience, Hart and Giszter (2010) addressed this question in an innovative way, by developing a new methodology linking the neural input to the motor output. They supported the hypothesis that modularity is directly embodied in the neural circuitry of the spinal cord.…”
Section: Review Of Hart and Gisztermentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study published in The Journal of Neuroscience, Hart and Giszter (2010) addressed this question in an innovative way, by developing a new methodology linking the neural input to the motor output. They supported the hypothesis that modularity is directly embodied in the neural circuitry of the spinal cord.…”
Section: Review Of Hart and Gisztermentioning
confidence: 99%
“…The neurons in the IZ depths (700 -800 m) thus qualified as putative interneurons and consequently, were selected for further analysis. The authors also looked at the neural activity in the shallowest depth (400 -500 m) and demonstrated that firing of neurons at that level were also uniformly better related to independent components than EMGs [Hart and Giszter (2010), their Fig. 3D], but only for firing in response to light touch stimulation: such a preference for independent components was not observed in responses to the other two types of stimuli [Hart and Giszter (2010), their Fig.…”
Section: Review Of Hart and Gisztermentioning
confidence: 99%
See 3 more Smart Citations